2010
DOI: 10.1177/147470491000800404
|View full text |Cite
|
Sign up to set email alerts
|

A New Viewpoint on the Evolution of Sexually Dimorphic Human Faces

Abstract: Human faces show marked sexual shape dimorphism, and this affects their attractiveness. Humans also show marked height dimorphism, which means that men typically view women's faces from slightly above and women typically view men's faces from slightly below. We tested the idea that this perspective difference may be the evolutionary origin of the face shape dimorphism by having males and females rate the masculinity/femininity and attractiveness of male and female faces that had been manipulated in pitch (forw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 27 publications
6
42
2
Order By: Relevance
“…For example, previous research has identified that male faces generally have longer and wider jaws, whereas female faces generally have smaller jaws and fuller lips (Burke & Sulikowski, 2010;Rhodes, 2006), but the heterosexual women in our sample had smaller lips, thinner lips, and a thinner mouth than heterosexual men. The mouth region was one of the regions that differed between lesbian and heterosexual women, andwe cannot rule out the Type II error explanation conclusively.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…For example, previous research has identified that male faces generally have longer and wider jaws, whereas female faces generally have smaller jaws and fuller lips (Burke & Sulikowski, 2010;Rhodes, 2006), but the heterosexual women in our sample had smaller lips, thinner lips, and a thinner mouth than heterosexual men. The mouth region was one of the regions that differed between lesbian and heterosexual women, andwe cannot rule out the Type II error explanation conclusively.…”
Section: Discussionmentioning
confidence: 70%
“…Sexual differentiation, however, is a common mechanism used to explain the development of facial structure because men and women differ in facial structure. Male faces generally have longer jaws, wider jaws, smaller eyes, larger noses, and more prominent brow ridges, whereas female faces generally have larger eyes, smaller brow ridges, smaller jaws, smaller chins, and fuller lips (Burke & Sulikowski, 2010;Rhodes, 2006). The development of the sexual dimorphism of faces is guided by both prenatal and postnatal factors (Bulygina, Mitteroecker, & Aiello, 2006;Enlow, 1982;Meindl, Windhager, Wallner, & Schaefer, 2012;Verdonck, Gaethofs, Carels, & de Zegher, 1999).…”
Section: Introductionmentioning
confidence: 98%
“…Whether this is a genuine difference in femininity or simply a perceived difference due to our participants' lack of familiarity with African faces (and with the features that distinguish male and female African faces) is impossible to tell from the current data, but it does provide a potential explanation for the lower attractiveness ratings given to female African faces, since lower perceived femininity is known to correlate with lower attractiveness ratings (e.g., Burke and Sulikowski, 2010). To properly tease out the factors…”
Section: Discussionmentioning
confidence: 86%
“…Recently , Schneider, Hecht and Carbon (2012) showed that persons with upward faces were perceived as heavier than persons with downward faces. Additionally, an upward posture increases the perceived masculinity of male targets (Burke & Sulikowski, 2010).…”
Section: Head Postures and Direct Eye Gazementioning
confidence: 99%